2012
DOI: 10.1371/journal.pone.0047676
|View full text |Cite
|
Sign up to set email alerts
|

Present Spatial Diversity Patterns of Theobroma cacao L. in the Neotropics Reflect Genetic Differentiation in Pleistocene Refugia Followed by Human-Influenced Dispersal

Abstract: Cacao (Theobroma cacao L.) is indigenous to the Amazon basin, but is generally believed to have been domesticated in Mesoamerica for the production of chocolate beverage. However, cacao’s distribution of genetic diversity in South America is also likely to reflect pre-Columbian human influences that were superimposed on natural processes of genetic differentiation. Here we present the results of a spatial analysis of the intra-specific diversity of cacao in Latin America, drawing on a dataset of 939 cacao tree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
139
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(152 citation statements)
references
References 46 publications
7
139
0
6
Order By: Relevance
“…Domestication of cocoa began around 8,000 years ago, in the foothills of the Andes, along the banks of major upper tributaries of the Amazon River in what is today Bolivia, Peru, Ecuador, and Colombia (Clement et al 2010;Miller and Nair 2006;Thomas et al 2012). Native Amazonians collected ripe cocoa pods from fruiting trees found in patches embedded within the forest matrix in the high terraces of the riverine system, and transported them back to their villages for home consumption.…”
Section: Domestication and Intensification Of Cocoamentioning
confidence: 99%
See 1 more Smart Citation
“…Domestication of cocoa began around 8,000 years ago, in the foothills of the Andes, along the banks of major upper tributaries of the Amazon River in what is today Bolivia, Peru, Ecuador, and Colombia (Clement et al 2010;Miller and Nair 2006;Thomas et al 2012). Native Amazonians collected ripe cocoa pods from fruiting trees found in patches embedded within the forest matrix in the high terraces of the riverine system, and transported them back to their villages for home consumption.…”
Section: Domestication and Intensification Of Cocoamentioning
confidence: 99%
“…Cocoa pods were consumed as fruit by sucking the pulp and spitting out the seed, or were fermented to produce an alcoholic drink (Henderson et al 2007). Early selection for desirable traits such as abundant and sweet pulp probably occurred (Thomas et al 2012).…”
Section: Domestication and Intensification Of Cocoamentioning
confidence: 99%
“…First, the mode of pollen and seed dispersal, which determines the N m among populations (Li et al, 2009a;Bellucci et al, 2011;Nestmann et al, 2011;Wang and Li, 2011), can facilitate N m among populations, minimizing the population differentiation. Many studies have demonstrated that wind-pollinated and wind-dispersed species exhibit low levels of genetic differentiation (Li et al, 2009b;Adamski et al, 2012;Thomas et al, 2012), approaching the levels observed in C. arborescens. Second, genetic diversity may be influenced by geographic distances, especially longitudinal differences, as revealed by the Mantel test.…”
Section: Genetic Structurementioning
confidence: 98%
“…An important step towards improving the on-farm conservation of any species is having data about its current (and potential) distribution and cultivation. In addition to individuals' knowledge on these aspects, publicly available georeferenced data is a powerful starting point for studies on a crop's agroecological potential and adaptive capacity which in turn are useful for planning in situ conservation initiatives [33][34][35]. Searches performed in the data portal of the GBIF resulted in retrieval of georeferenced data for almost all the species.…”
Section: Limited Knowledge On the Species' Distribution And Productionmentioning
confidence: 99%